Can I go home now? The safety and efficacy of a new UK paediatric febrile neutropenia protocol for risk-stratified early discharge on oral antibiotics. Issue 3 (12th December 2022) - Jackson, Thomas John; Napper, Rachel; Haeusler, Gabrielle M; Pizer, Barry; Bate, Jessica; Grundy, Richard G; Samarasinghe, Sujith; Angelini, Paola; Ball-Gamble, Ashley; Phillips, Bob; Morgan, Jessica Elizabeth
Abstract : Objective: To evaluate a new protocol of risk stratification and early discharge for children with febrile neutropenia (FN). Design: Prospective service evaluation from 17 April 2020 to 16 April 2021. Setting: 13 specialist centres in the UK. Patients: 405 children presenting with FN. Intervention: All children received intravenous antibiotics at presentation. Risk stratification was determined using the Australian-UK-Swiss (AUS) rule and eligibility for homecare assessed using criteria including disease, chemotherapy, presenting features and social factors. Those eligible for homecare could be discharged on oral antibiotics after a period of observation proportional to their risk group. Main outcome measures: Median duration of admission and of intravenous antibiotics, and percentage of patients with positive blood cultures, significant infection, readmission within 7 days of initial presentation, intensive care unit (ICU) admission, death from infection and death from other causes. Results: 13 centres contributed 729 initial presentations of 405 patients. AUS rule scores were positively correlated with positive blood cultures, significant infection, ICU admission and death. 20% of children were eligible for homecare with oral antibiotics, of which 55% were low risk (AUS 0–1). 46% low-risk homecare eligible patients were discharged by 24 hours vs 2% homecare ineligible. Homecare readmission rates were 14% overall and 16% for low-risk cases (similar to a meta-analysis of previous studies). No child eligible for homecare was admitted to ICU or died. Conclusions: Use of the AUS rule and homecare criteria allow for safe early outpatient management of children with FN.